PEMANFAATAN LIMBAH KULIT JERUK NIPIS (Citrus aurantifolia) DAN SERBUK KOPI ARABIKA (Coffea sp) DALAM FORMULASI PEMBUATAN LULUR TRADISIONAL TAHUN 2022 - sulasmi sulasmi (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Lime peel and coffee grounds are good natural ingredients and have the potential to be used as cosmetic preparations, one of which is used to make body lulur preparations because lime peel contains vitamin C which can absorbs oil from the skin and removes dead skin cells so that the skin looks cleaner, softer and brighter, while the brewed coffee grounds have antioxidant activity, which contains 3.88% of antioxidants and 1-1.5% of caffeine contained in coffee grounds. This study aims to determine which lime peel and coffee grounds can lighten the skin in 2 weeks and to find out which formulation is the best. The lulur acceptability test includes a softness test, iritation test, ease of cleaning and skin brightness. then the lulur was tested for acceptability during week 0 to week 2. Based on the graph, formulation I with a concentration of 5%:10%, formulation II with a concentration of 10%:5% and formulation III with a concentration of 10%:10% are significant formulas for brightening the skin of some respondents. So it can be concluded that there is an effect of skin tone on the use of body lulur preparations at room temperature during week 0 to week 2.